2022
DOI: 10.1371/journal.pone.0269639
|View full text |Cite|
|
Sign up to set email alerts
|

Inequities in the incidence and mortality due to COVID-19 in nursing homes in Barcelona by characteristics of the nursing homes

Abstract: Background Residents of Nursing Homes (NHs) have suffered greater impacts from the COVID-19 pandemic. However, the rates of COVID-19 in these institutions are heterogeneously distributed. Describing and understanding the structural, functional, and socioeconomic differences between NHs is extremely important to avoid new outbreaks. Objectives Analyze inequalities in the cumulative incidences (CIs) and in the mortality rates (MRs) due to COVID-19 in the NHs of Barcelona based on the characteristics of the NHs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…A large international literature has identified a number of factors associated with Covid-19 outbreaks in LTRC settings including facility size, form of ownership and community rates of Covid-19 (Konetzka et al, 2021;Frazer et al, 2021). Larger LTRC homes (Aalto et al, 2022;Konetzka et al, 2021) and homes with higher rates of occupancy (Dutey-Magni et al, 2021;Torres et al, 2022) have been found to have more Covid-19 outbreaks and higher Covid-19 mortality rates. Although the probability of an outbreak increased with the size of the facility, higher nurse-resident ratios were shown to reduce spread of Covid-19 infection once it entered a facility (Dutey-Magni et al, 2021;Figueroa et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…A large international literature has identified a number of factors associated with Covid-19 outbreaks in LTRC settings including facility size, form of ownership and community rates of Covid-19 (Konetzka et al, 2021;Frazer et al, 2021). Larger LTRC homes (Aalto et al, 2022;Konetzka et al, 2021) and homes with higher rates of occupancy (Dutey-Magni et al, 2021;Torres et al, 2022) have been found to have more Covid-19 outbreaks and higher Covid-19 mortality rates. Although the probability of an outbreak increased with the size of the facility, higher nurse-resident ratios were shown to reduce spread of Covid-19 infection once it entered a facility (Dutey-Magni et al, 2021;Figueroa et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The environmental factors frequently emerged and supported by a substantial body of evidence linked to outbreaks include a higher number of beds, occupancy rate [21,25,26,30,31,34,47,54,56,60,61,63,65,67,72,73,[82][83][84]91,94,97,106], presence of outbreaks in surrounding counties/communities [6,26,[29][30][31]37,38,60,69,79,80,84,91,93,99,104], high-density communities [21,29,56,67,73,106] socioeconomic status of the community, [24,64,77,84,…”
Section: Environmental Factors Related To Covid Outbreaksmentioning
confidence: 99%
“…The environmental factors frequently associated with mortality include occupancy, levels of crowding [2,25,56,64,83,94,98,104], the larger size of the facility or the number of beds in the LTCF [2,32,33,62,63,65], the location of the LTCF [2,21,24,62,87], higher community or county incidences [60,77,80,104,113], and structural design of the rooms or number of beds in a room [21,25,66,113].…”
Section: Environmental Factors Related To Covid-related Deathsmentioning
confidence: 99%
“…In Wales, longitudinal cohort analyses has examined risk factors for infections, including age, community prevalence and hospital admission [ 15 , 16 ]. Internationally, variables such as neighbourhood socio-economic position, occupancy, ownership and crowding have been examined [ 6 , 17–19 ]. Although international comparisons are complicated by structural and contextual differences in the configuration of care services [ 20 ], large care-home outbreaks are a common feature of periods whenever COVID community incidence is high [ 21 ].…”
Section: Introductionmentioning
confidence: 99%